Bangpungtongsung-san alleviates depressive-like behavior and metabolic disturbances in high-fat diet-induced obesity: mechanisms involving inflammation, CREB/BDNF signaling, and NMDA receptor modulation - Lee, Bo-Ram; Kim, No Soo; Bae, Ui-Jin; Choi, Yujin; Yang, Changsop; Lee, Mi Young (Frontiers in Pharmacology, 2025)
IntroductionBangpungtongsung-san (BTS) is a traditional multi-herb preparation prescribed for obesity, but its role in obesity-associated depression remains unclear. We evaluated whether BTS alleviates depressive-like behaviors in high-fat diet (HFD) induced obese mice and elucidated the underlying mechanisms of its antidepressant potential.MethodsMale C57BL/6N mice were randomized to normal diet (ND) or continuous HFD and maintained for 10 weeks. Throughout this period, mice were orally treated with BTS (30, 100, or 300 mg/kg), fluoxetine (FXT), simvastatin (SIM), or vehicle under identical chronic regimens. Body weight was monitored weekly. At week 10, metabolic parameters (blood glucose, plasma total cholesterol, triglycerides, HDL-C, and leptin) and depressive-like behaviors (tail suspension test and forced swimming test) were assessed. Subsequently, mechanistic analyses were performed to determine the effects of BTS on systemic and brain inflammatory responses, BDNF signaling, NMDAR expression, and serotonin (5-HT) signaling (Ido1, Tph2, and SERT) in the prefrontal cortex (PFC) and hippocampus (HPC).ResultsA 10-week continuous HFD feeding produced robust weight gain, hyperglycemia, and elevated levels of total cholesterol (TCHO), triglycerides (TG), HDL-C, and leptin. Oral BTS treatment attenuated body weight gain and reversed these HFD-induced metabolic abnormalities (TCHO, TG, HDL-C, and leptin) in blood. Behaviorally, BTS-treated mice exhibited reduced immobility time compared to HFD group, indicating antidepressant-like effects. Mechanistically, BTS reduced systemic and brain pro-inflammatory cytokines (IL-1β and TNF-α) and normalized hippocampal GluN1/GluN2A/GluN2B protein levels together with BDNF expression restoration. BTS also elevated whole-brain 5-HT and tended to regulate SERT expression in HPC, supporting the enhanced synaptic 5-HT availability. Under identical chronic oral conditions, FXT showed partial antidepressant efficacy with minimal metabolic benefits, whereas SIM exhibited moderate metabolic improvements with limited behavioral effects. Comparatively, BTS provided superior therapeutic outcomes across both behavioral and metabolic parameters.ConclusionBTS ameliorated depression-like behaviors and metabolic dysfunction in HFD-induced obesity through coordinated modulation of inflammation, BDNF signaling, NMDAR expression, and 5-HT neurotransmission in the HPC. These findings support BTS as a promising multi-target candidate for treating comorbid depression and obesity.